Involvement of nitrogen in storage root growth and related gene expression in sweet potato (Ipomoea batatas). (26th February 2020) - Yao, Z.; Wang, Z.; Fang, B.; Chen, J.; Zhang, X.; Luo, Z.; Huang, L.; Zou, H.; Yang, Y.
Abstract: Nitrogen (N) could affect storage root growth and development of sweet potato. To manage external N concentration fluctuations, plants have developed a wide range of strategies, such as growth changes and gene expression. Five sweet potato cultivars were used to analyse the functions of N in regulating storage root growth. Growth responses and physiological indicators were measured to determine the physiological changes regulated by different N concentrations. Expression profiles of related genes were analysed via microarray hybridization data and qRT‐PCR analysis to reveal the molecular mechanisms of storage root growth regulated by different N concentrations. The growth responses and physiological indicators of the five cultivars were changed by N concentration. The root fresh weight of two of the sweet potato cultivars, SS19 and GS87, was higher under low N concentrations compared with the other cultivars. SS19 and GS87 were found to be having greater tolerance to low N concentration. The expression of N metabolism and storage root growth related genes was regulated by N concentration in sweet potato. These results reveal that N significantly regulated storage root growth. SS19 and GS87 were more tolerant to low N concentration and produced greater storage root yield (at 30 days). Furthermore, several N response genes were involved in both N metabolism and storage root growth. Abstract : N significantly affected sweetpotato growth and related gene expression, which also provide further understanding about the mechanism of sweetpotato adaptation to external N concentration fluctuations.